Komposisi Mangrove pada Lahan Tercemar BTEX dan Logam Berat - Indawan, Edyson; Ahmadi, Kgs.; Novitawati, Retno Ayu Dewi (Jurnal Natur Indonesia, 2012)
The study was aimed to gasp inventory an expired plant mangrove species characteristic respectively collection specimen land us function BTEX and heavy metal at growth environment. The study held from April through November 2007. Design with two classes, Rank I : survey activities and explored in land for quantity and identification, Rank II : Analysis totality solid matter petroleum level BTEX and heavy metal situ by research in location. The results of mangrove identification (main component, supporting component, and associated mangrove) showed there are 11 families and 25 species. BTEX parameter from soil sample was detected benzene intensive contamination on Andil river (16.30 ppm), Porangan river (81.30 ppm), Gombal river (56.90 ppm), Kacar river (36.90 ppm) but it was not detected on Krondo river. Toluene intensive contamination Porangan river (824 ppm) and Kacar river (896 ppm). BTEX parameter from water sample was detected benzene intensive contamination on Andil river (24.30 ppm), Porangan river (8.13 ppm), Gombal river (20.30 ppm), Kacar river (8.13 ppm), Krondo river (8.13 ppm), and Toluene contaminate slightly. Ethylbenzene and xilene were not detected by gas chromatography. Soil medium showed that contamination mainly Pb on Gombal river (5.98 mg/Kg), Kacar river (7.24 mg/Kg) and Krondo river (6.43 mg/Kg), where are Andil river and Porangan river were only slightly contaminated. The metal occurred on Cu for all, except Andil river (6.22 mg/Kg), whereas Zn and Cr did not contaminate, while Ag and Cd were not detected. Water medium was not contaminated by Pb, Cd, Cr, and Zn, furthermore Ag and Cu were not detected